Rancang Bangun Sistem Pendeteksi Suhu Air Pada Lahan Rumput Laut Berbasis Atmega 328 - Baso Ali; Iin Putri Karmila Karsa; Andi Rosman N. (Universitas Negeri Makassar, 2022)
Abstract. The study designed a seaweed water temperature detection device based on atmega 328 microcontrollers connected with sensors. The type of research is Research and Development (R&D) using a 4D development model. The research site was conducted on seaweed cultivation land located around campus II of Cokroaminoto Palopo University. Development of Atmega 328-based seaweed temperature detection tool through several stages, namely 1) defining / define, 2) design / design, 3) Development / develop, 4) Spread / disseminate. The results showed that the Atmega 328-based temperature detection device had worked well. Based on the results of validation by two experts related to the feasibility of atmega 328-based temperature measuring instrument obtained the result that the temperature measuring instrument is in the category is very good to use. This is evident from quantitative data and validator questionnaire stuffing and is supported by constructive comments and suggestions from each expert validator. The conclusion of validation results that the measuring instrument is worth testing in the field or at the research site.